ChemInform Abstract: Synthesis of Highly Basic Hexasubstituted Biguanides by Environmentally Friendly Methods. Issue 16 (22nd April 2014) - Glasovac, Zoran; Troselj, Pavle; Jusinski, Iva; Margetic, Davor; Eckert‐Maksic, Mirjana
Abstract Various methods such as high speed vibrational milling, high pressure, ultrasound, microwave irradiation, and conventional heating conditions are employed for the reaction of tetramethylguanidine with carbodiimides.